Challenges in the decarbonization of the energy sector. (15th August 2020) - Papadis, Elisa; Tsatsaronis, George
Abstract: In order to limit the effects of climate change, the carbon dioxide emissions associated with the energy sector need to be reduced. Significant reductions can be achieved by using appropriate technologies and policies. In the context of recent discussions about climate change and energy transition, this article critically reviews some technologies, policies and frequently discussed solutions. The options for carbon emission reductions are grouped into (1) generation of secondary energy carriers, (2) end-use energy sectors and (3) sector interdependencies. The challenges on the way to a decarbonized energy sector are identified with respect to environmental sustainability, security of energy supply, economic stability and social aspects. A global carbon tax is the most promising instrument to accelerate the process of decarbonization. Nevertheless, this process will be very challenging for humanity due to high capital requirements, the competition among energy sectors for decarbonization options, inconsistent environmental policies and public acceptance of changes in energy use. Highlights: Review of technological options for decarbonizing each energy sector. Challenges include economic & social issues, energy supply security & sustainability. A global carbon tax can accelerate the decarbonization process. Long-term decision making in energy & political stability need to be ensured. The competing energy sectors need to be prioritized for decarbonization.